Muro-ami ([Quezon City] ABS-CBN, 1986)
Shows the fishing method, muro-ami, which was introduced by Japanese fishermen in the 1930's. The cases of two fishing corporations, the Frabal Shipping and Ice Plant Corp. and the OSLOB owned by the Abines family were discussed. The Philippine government is taking into consideration the banning of muro-ami.
VHS
Keywords: Fishing; Fisheries; Sociology